Concurrent chemoradiation therapy with Docetaxel/Cisplatin followed by Docetaxel consolidation therapy in inoperable stage IIIA/B non-small-cell lung cancer: results of a phase I study - Huber, Rudolf M.; Borgmeier, Astrid; Flentje, Michael; Willner, Jochen; Schmidt, Michael; Manegold, Christian; Bramlage, Peter; Debus, Jürgen (Clinical lung cancer, 2010)
Introduction - Docetaxel consolidation therapy (DCT) after concurrent cisplatin/docetaxel chemoradiation therapy (CRT) produces high tumor control in non-small-cell lung cancer (NSCLC); toxicity is, however, considerable. We aimed to determine the maximally tolerated dose (MTD) for DCT. - Patients and Methods - Patients with inoperable stage IIIB NSCLC received docetaxel 20 mg/m2 and cisplatin 25 mg/m2 on days 1, 8, 15, 22, 29, and 36, with concurrent radiation therapy 5 days per week for a total dose of 66 Gy. Patients achieving stable disease, partial response, or complete response were given DCT on days 71, 92, and 113. DCT was started with 75 mg/m2 and titrated depending on tolerability. The MTD of docetaxel was defined as the dose preceding that at which 3 or more patients experienced dose-limiting toxicity (DLT). - Results - Of 23 patients enrolled (median age, 58.8 years ± 7.3 years), 19 received complete CRT (4 withdrew because of toxicity). Of the patients receiving complete CRT, 1 patient died and 1 became operable, leaving 17 patients eligible for DCT starting at 75 mg/m2. After the third patient with DLT, dose was reduced to 60 mg/m2. Median survival was 27.6 months ± 23.1 months. Median TTP was 12.4 months ± 10.7 months. - Conclusion - The MTD of DCT after concurrent cisplatin/docetaxel CRT was determined to be 60 mg/m2, but toxicity was considerable. The benefit-risk ratio of DCT has, however, been questioned by a placebo-controlled phase III trial. Further phase III trials need to consider further stratification factors (pretreatment forced expiratory volume [FEV]1, hemoglobin, performance, and stage) to define a role for DCT in patients with NSCLC.